Cases in intelligence analysis structured analytic techniques in action - Beebe, Sarah Miller (CQ Press, 2012)
This book of cases will contain 12 cases of approx 24pp each. It is part of a larger case archive of (initally) about 20 cases. 12 cases will be in the book; all 20 will be online. See related project: Cases in Intelligence: Online Case Archive.